Potentiating Effects of Accentuated Eccentric Loading Are Dependent Upon Relative Strength. Issue 5 (May 2021) - Merrigan, Justin J.; Tufano, James J.; Jones, Margaret T.
Abstract : Abstract: Merrigan, JJ, Tufano, JJ, and Jones, MT. Potentiating effects of accentuated eccentric loading are dependent upon relative strength. J Strength Cond Res 35(5): 1208–1216, 2021—The purpose was to evaluate the acute effects of accentuated eccentric loading (AEL) on bench press velocity and subsequent perceived effort (ratings of perceived exertion [RPE]) and soreness. Resistance-trained men ( n = 8) and women ( n = 2) completed 4 sets of 5 bench press repetitions with AEL and traditional loading (TL) using concentric loads of 50% (AEL50, TL50) and 65% (AEL65, TL65) 1-repetition maximum (1RM). Throughout each TL set, the eccentric load remained identical to the concentric. Variable resistance during the first repetition of AEL equaled 120% 1RM. Hierarchical Linear Modeling was used to evaluate differences between AEL and TL ( p < 0.05). For the first repetition, AEL50 and AEL65 resulted in slower eccentric and concentric velocities. The increasing slope of eccentric and concentric velocity across repetitions was greater during AEL50 and AEL65 compared with TL50 and TL65, respectively ( p < 0.05). As an individual's strength increased, AEL50 resulted in slower eccentric velocity and faster concentric velocity than TL50. The AEL65 resulted in faster concentric velocity than TL65 ( p < 0.05). Mean protocol comparisons revealed trivial to small effects between AEL and TL. There were no differences in RPE or soreness between protocols with soreness ratings remaining unchanged from baseline (1.80 ± 0.20 AU; p < 0.05). Overall, AEL was not effective for increasing concentric velocity during the bench press with current loading protocols. Yet, stronger individuals may exhibit increases in concentric velocity from AEL, which may be a result of different pacing strategies employed during the eccentric phase. Furthermore, when using the current AEL protocols, eccentric intensities were increased with no greater RPE or soreness.